The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations CHILDREN CHILDREN ARE HAPPIEST WHEN THEY ARE BUSY Give them home occupations and hobbies; encourage games and school interests, and you won't have the neighbours complaining of noise or broken fences. Quite small children can "help mother" and many cleanliness lessons can be taught as part of the game. THINK OF THE FUTURE Train the children in good health habits, with as few rules as possible. Cleanliness, rightly chosen food and plenty of rest and fresh air will build healthy young men and women. WASH ALL OVER AFTER GAMES At all modern games fields there are facilities for washing; hot and cold water, spray baths and soap are provided. Children sometimes have to bring their own towels. Make sure that the child's name is clearly marked and warn against lending or borrowing towels. If they have to come home without changing after games, see that they wash all over and change as soon as they are in. [Image with caption] Let the toddlers wash themselves. CLOTHES MOTHS ARE EXPENSIVE PETS TO KEEP IN A WARDROBE Turn out cupboards and wardrobes frequently. Do not accumulate rubbish or worn-out clothing. Keep clothes you are storing in tin boxes or well wrapped in newspaper. Moth balls or powdered alum can be used as a preventive of moths. 15 177/5/8/2